INFLUENCE OF FINANCIAL LITERACY, MANAGERIAL EXPERIENCE ON FINANCIAL MANAGEMENT PERFORMANCE OF SMES IN SURABAYA - Olivia Aurelia Heryanto; Pwee Leng (Finance and Investment Program, School of Business and Management - Petra Christian University, 2021)
This study aims to determine the effect of financial literacy and managerial experience on financial management performance of SMEs. The data collection technique in this study was using a questionnaire distributed to 400 SME owners in Surabaya. The data that has been collected is then processed by the logistic regression analysis method using the software IBM SPSS Statistics 25. The results show that financial literacy and managerial experience variables significantly affect financial management performance variables.